Lawrence Sidney Thompson correspondence - Thompson, Lawrence S. (Lawrence Sidney), 1916-1986.
Correspondence between Thompson and James Bennett Childs relating to libraries, especially to U.S. and foreign government documents and their use internationally.
Librarian and scholar.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Childs, James B. -- 1896-1977 -- Correspondence; Government publications; Government publications -- United States; Libraries; Librarians; Scholars